Diseño de un producto turístico para el aprovechamiento del potencial de los recursos naturales y culturales en el Humedal La Segua, cantón Chone y Tosagua - Basurto Araúz, María Elena (2015)
The present work aims to design a tourist product for a better use of the natural and cultural resources in the Segua wetland, Chone and Tosagua canton, it was taken as reference the methodology of Dr. Esther Lidia Machado Chaviano and Yanet Hernandez 2007, it covers entirely the subject of study, once structured the methodology a survey of general information about the parish of San Antonio in Chone Canton was applied, the starting point the arrival of the La Segua wetland and where is was held 75 % of the attrction, then a diagnosis of the current situation of La Segua Wetland with their respective tourist inventory, using the SWOT matrix to analyze weaknesses, threats, strengths and opportunities that exist in the wetland with the information collected is determined proceeded to market research by surveying visitors to the wetland and interviews with the owners. The respective slogan, logo and itinerary was designed and the marketing mix was determined with their own strategies. It can be concluded that there is an interest from the competent authorities in preserving the wetland's ecosystem otherwise the product designed is considered feasible for the community, local government and participants. They believe that it may help the development of the cantons where the resource is located, they are interested in getting involved in tourism.